A strategy for programming the regulation of in vitro transcription with application in molecular circuits. Issue 10 (8th March 2021) - Hu, Yingxin; Xie, Chun; Xu, Fei; Pan, Linqiang
Abstract : A strategy for programming the regulation of in vitro transcription with a variable number of inputs was proposed. Based on this strategy, various circuits such as logic circuits, parallel transcription circuits, and cascading circuits were constructed. Abstract : In vitro transcription is a convenient platform for fabricating nanodevices and has been used for assembling synthetic networks. However, it remains challenging to regulate synthetic cell-free in vitro transcription by multiple stimuli in a simple and programmable way. We proposed a strategy to regulate in vitro transcription by controlling the transcription templates' promoter domain via variable DNA inputs. To demonstrate the utility of this strategy, various logic circuits and cascading circuits were implemented. With the advantage of simplicity, modularity, programmability, and extensibility, the proposed strategy has potential in biocomputing, bioanalytical, and therapeutic applications.